Was ist die Standardform von y = (x - 1) (x -5) (x + 3)?

Was ist die Standardform von y = (x - 1) (x -5) (x + 3)?
Anonim

Antworten:

#y = x ^ 3 -3x ^ 2 -13x + 15 #

Erläuterung:

Gegeben: #y = (x - 1) (x - 5) (x + 3) #

Verteilen Sie die ersten beiden Faktoren mit FOIL:

#y = (x ^ -5 - -1x + 5) (x + 3) #

Fügen Sie ähnliche Begriffe hinzu: # "" y = (x ^ 2 -6x + 5) (x + 3) #

FOIL nochmal:

#y = x ^ 3 -6x ^ 2 + 5x + 3x ^ 2 -18x + 15 #

Fügen Sie ähnliche Begriffe hinzu: # "" y = x ^ 3 -3x ^ 2 -13x + 15 #